Quasicausal expansion of the quantum Liouville propagator - Bund, G. W. [UNESP]; Mizrahi, S. S.; Tijero, M. C. [UNESP] (American Physical Society (APS), 1996)
The quasicausal expansion of the quantum Liouville propagator is introduced into the Weyl-Wigner picture. The zeroth-order term is shown to lead to the statistical quasiclassical method of Lee and Scully [J. Chem. Phys. 73, 2238 (1980)]. © 1996 The American Physical Society.